Environmental impact assessment for sustainable development in the Commonwealth Caribbean: an overview. - Moss, S.G. (UWI. Faculty of Law Library, 2011)
Provides an overview with sources of information on the topic. Concludes that Environmental Impact Assessment requires a holistic and ethics-based decisionmaking system which looks towards a new philosophical and ecological ethic.
Keywords: ENVIRONMENTAL MANAGEMENT; CARIBBEAN; SUSTAINABLE DEVELOPMENT